Fostering Clinical Reasoning in Nursing Students. (January 2015) - Koharchik, Linda; Caputi, Linda; Robb, Meigan; Culleiton, Alicia L.
Abstract : This article is one in a series on the roles of adjunct clinical faculty and preceptors, who teach nursing students to apply knowledge in clinical settings. This article describes why it's important that nursing students develop clinical reasoning skills and how clinical nursing instructors can help them learn these skills. Abstract : This article in a series on the roles of adjunct clinical faculty and preceptors describes how instructors can help nursing students develop clinical reasoning skills.